EFFECT OF PART REPLACEMENT OF SILICA SAND WITH CARBON BLACK ON COMPOSITE PROPERTIES: ?Short Communication (Biological Sciences - PJSIR, 2003)
Much interest have been shown in the study of filled natural rubber composites (Bristow 1986; Elliot 1986; Barker 1987; Adu and Adeosun 1997; Adeosun et al 1999). We have re- ported the properties of natural rubber filled with locally available materials (Adu et al 2000). The effect of local clay, limestone, silica sand and charcoal on the properties of natu- ral rubber has been examined. Results have shown detrimen- tal effects of silica sand on the properties of natural rubber compound. It has been reported that when silica is used as a part for part replacement of carbon black, the heat build up the composite decreased whilst tear resistance improved (Horn 1975; Barbin and Rodgers 1994).